Efficacy of motivational enhancement therapy on alcohol use disorders in patients with chronic hepatitis C: a randomized controlled trial. (14th August 2014) - Dieperink, Eric; Fuller, Bret; Isenhart, Carl; McMaken, Kelly; Lenox, Rebecca; Pocha, Christine; Thuras, Paul; Hauser, Peter
Abstract Aims To determine the efficacy of motivational enhancement therapy (MET) on alcohol use in patients with the hepatitis C virus (HCV) and an alcohol use disorder (AUD). Design Randomized, single‐blind, controlled trial comparing MET to a control education condition with 6‐month follow‐up. Setting Patients were recruited from hepatitis clinics at the Minneapolis, Minnesota and Portland, Oregon Veterans Affairs Health Care Systems, USA. Participants and Intervention Patients with HCV, an AUD and continued alcohol use (n = 139) were randomized to receive either MET (n = 70) or a control education condition (n = 69) over 3 months. Measurements Data were self‐reported percentage of days abstinent from alcohol and number of standard alcohol drinks per week 6 months after randomization. Findings At baseline, subjects in MET had 34.98% days abstinent, which increased to 73.15% at 6 months compared to 34.63 and 59.49% for the control condition. Multi‐level models examined changes in alcohol consumption between MET and control groups. Results showed a significant increase in percentage of days abstinent overall (F(1120.4) = 28.04, P < 0.001) and a significant group × time effect (F(1119.9) = 5.23, P = 0.024) with the MET group showing a greater increase in percentage of days abstinent at 6 months compared with the education control condition. There were no significant differences between groups for drinks per week. The effect size of the MET intervention was moderate (0.45) for percentage of days abstinent. Conclusion Motivational enhancement therapy (MET) appears to increase the percentage of days abstinent in patients with chronic hepatitis C, alcohol use disorders and ongoing alcohol use.